“Aku dan Bapa Adalah Satu” (Analisis Teologis Yohanes 10:30) - Tobing, Lucia J. L.; Sihombing, Warseto Freddy (Prodi Teologi IAKN Tarutung, 2024)
Jesus in John 10:30 said: “I and the Father are one” - a statement that offended the Jews at that time because Jesus equated Himself with God (Yahweh). Through qualitative research methods, the author explores the meaning of Jesus’ statement. The purpose and intent of Jesus' statement was so that every believer, both at that time and in the future, would pay more serious attention to His words that showed His divinity. It is understandable that Jesus’ statement about Himself that He and God the Father are one (the same) invites everyone to conclude that He sees Himself as equal to God. Jesus’ claim to be equal to the Father is true and proven (John 14:1). Jesus positions Himself as the object of faith of every believer. Seeing the evidence of Jesus' equality with the Father in John 14:10b, he said that what I say to you I do not speak on my own authority, but the Father who dwells in Me does His works. So when Jesus speaks, the Father works through him. Jesus in His statements repeatedly said that the Father dwells in Him, and Jesus only does the work of His Father.